Staphylococcus aureus Bacteremia in a Secondary Level Spanish Hospital: Clinical Implications of Vancomycin MIC≥2 Isolates. (4th October 2017) - Abelenda, Gabriela; Corbacho, María Dolores; Núñez, Ruth; Cervero, Miguel
Abstract: Background: The relationship between microbiological and clinical data in S. aureus bacteremia is a critical point to establish new therapeutic strategies that modify the prognosis of this entity. The high Vancomycin MIC has to do with the thickness of the bacterial wall and its resistance to the entry of this antibiotic. This parameter could be a marker of poor clinical prognosis of S. aureus bacteremia. Methods: Retrospective descriptive study (January 2014–September 2016). 138 records were collected from the blood culture Severo Ochoa University Hospital registry. 31 cases with <8 weeks of difference between them and 9 with incompleted data, were excluded. 98 cases were analyzed through electronic clinical records. Microbiological analysis of Vancomycin MIC was performed using a microdilution technique. Statistical analysis was performed using SPSS 20.0 package using: Shapiro–Wilk, χ 2, U of Mann Whitney, logistic regression and Kaplan Meier. Results: The mean age was 71.41 with 59.2% of men and 40.8% of women. 63.3% of the patients had a Charlson comorbidity index≥6. A total of a 26.53% were carriers of a venous central catheter (VVC).The most frequent source of bacteremia was VVC with 26.5%, followed by primary bacteremia (22.4%), osteoarticular site (13.3%) and peripheral catheter (11.2%). The 77.55% of the episodes were health care related and 52.04% were nosocomial. A 41.8% of the patients had a complicated evolution but only a 14.24% were directly attributable to bacteremia. The 23.5% of patients needed admission in ICU. The admission in ICU was related with the delay in starting the correct antibiotic therapy ( P = 0.06).The global mortality rate at 30 days was 25.5% and the related mortality rate at 30 days was 18.4%. The 43.87% of the S. aureus had a MIC≥2 to Vancomycin (20 MRSA and 23 MSSA). The Vancomycin MIC≥2 was significantly associated with persistent bacteremia (P = 0.05), this statistic trend is maintained in the subgroup of MSSA (P = 0.09), but not in the subgroup MRSA (P = 0.56). There was no significant association between Vancomycin MIC ≥ 2 with high Charlson's comorbidity index, direct complications or-related mortality. Conclusion: Vancomycin MIC≥2 may be a useful parameter in daily clinical practice as a marker of poor clearance of bacteremia ( P = 0.05). In our series, this trend is maintained in MSSA subgroup but not in MRSA subgroup. Disclosures: All authors: No reported disclosures.